Antisemitism in North America New World, Old Hate - Baum, Steven K.; Kressel, Neil J.; Cohen, Florette; Jacobs, Steven Leonard (Jewish Identities in a Changing World, 2016)
In Antisemitism in North America, leading scholars offer a wide variety of perspectives on why the Jews in North America have sometimes faced considerable bigotry but have, in general, found a home far more hospitable than the ones they left behind in Europe. ; Readership: Those who are interested in a scholarly understanding of prejudice antisemitism, Jewish studies, hate studies, religious studies, cultural studies, Holocaust and genocide studies, social psychology and social sciences.